New findings on the issuance and use of fractional paper money in Puerto Rico (19th century) - Crespo Armáiz, Jorge L. (Documenta & Instrumenta - Documenta et Instrumenta, 2026)
The island of Puerto Rico is considered to be the first Spanish jurisdiction in the New World to issue provisional paper money, as early as 1766. The continuous interruptions in the remit-tances from the “Situado Mejicano” assigned to the island led the local authorities to resort to such emergency issuances on multiple occasions. By the beginning of the nineteenth century, with the definitive cessation of the “situados” after Mexican independence, the issuance of provisional “pa-peletas” reached the figure of 500.000 pesos, in different denominations. Although recent research has documented the issuance of provisional notes in fractional denominations towards the end of the eighteenth century, to date the design and iconographic characteristics of the fractional notes of one and half real of the issues of 1813 and 1814 were unknown. This study presents and analyzes unpublished official documentation that includes, for the first time, graphic evidence of the design of these fractional paper money. These findings also confirm the authenticity of “papeletas” of two reales from 1814, which since 1934 were considered false and now it is verified that they coincide with the official design circulated in the order of Governor Salvador Meléndez Bruna, documented here for the first time.